Is RED-S in athletes just another face of malnutrition?. (April 2022) - Peklaj, Eva; Reščič, Nina; Koroušic´ Seljak, Barbara; Rotovnik Kozjek, Nada
Summary: Background & aims: Relative energy deficiency syndrome in sport (RED-S) can impair the function of several body systems, resulting in short and long-term threats to athletes' health and performance. Research showed that these health and performance problems are often unrecognized, and the treatment is not adequate. The retrospective study presented in this paper aims to determine the prevalence of RED-S-related symptoms in a sample of Slovenian competitive athletes from various sports. Methods: We performed retrospective research based on a database of 150 athletes, aged from 14 to 34, who had nutritional assessments as a part of their medical examination. Data were collected, refined and statistical analysis was performed. 77 women and 73 men were included; 113 were classified as young athletes (14–21 years) and 37 as elite athletes (more than 21 years). Results: The majority (87%) of the athletes demonstrated at least one health-related symptom described by the RED-S-model; only 9% female and 18% male did not have any symptoms of RED-S. The number of different body systems with the compromised function was significantly higher (p < 0.001) in female athletes (2.9 ± 0.2) in comparison to male athletes (1.6 ± 0.1). For other health-related symptoms, there are statistically significant differences between young and elite athletes (p = 0.03), between female and male athletes (p = 0.02) and between young and elite female athletes (p = 0.01). When comparing groups by the number of all RED-S related symptoms, female athletes were more affected (p = 0.02). According to the RED-S CAT tool, the majority of athletes (64%) were classified in the yellow group, 7% of athletes have severe health and performance problems and fulfil criteria for the red group, and only 29% were classified in the green group. Conclusions: A high prevalence of RED-S-related symptoms in our sample competitive athletes indicates the high prevalence of nutrition-related medical problems in young and elite athletes. Therefore, it is necessary to incorporate nutritional risk screenings as a part of regular medical examinations of athletes. In addition, appropriate treatments for competitive athletes should be readily accessible, even for young athletes. It seems that the youth athlete population is the most endangered for developing malnutrition-related health problems. At the same time, we urgently need a more specific and simple nutritional screening tool that will allow us to identify athletes at nutritional risk or athletes who have RED-S.